A comprehensive study on RF MEMS switch - Jaafar, Haslina; Beh, Kean Sheng; Md Yunus, Nurul Amziah; Wan Hasan, Wan Zuha; Shafie, Suhaidi; Sidek, Othman (Springer, 2014)
This paper emphasis on state-of-the-art of the earlier until the current trend and demand, principles, design considerations, key performance and fabrication technology of RF MEMS switch devices developed over the past few years. RF MEMS switch performance and features such as actuation voltage, insertion loss, isolation and ease with cost of fabrication and applications are compared and discussed.